Lazer e educação popular: perspectivas de participantes-egressos/as de um projeto social - Santos, Matheus Oliveira (Universidade Federal de São Carlos, 2025)
The university extension project Experiences in Diversified Leisure Activities (VADL), linked to the Department of Physical Education and Human Motricity at the Federal University of São Carlos (UFSCar), aims to provide education by and for leisure to children and teenagers between 7 and 17 years of age from vulnerable communities in São Carlos, São Paulo, Brazil. Guided by the principles of Popular Education, VADL develops activities that value ethnic-racial, gender, intergenerational, and environmental relations. Its theoretical-methodological framework articulates Dialogical Pedagogy, the Science of Human Motricity, Existential Phenomenology, and the Ecology of Knowledges. This doctoral thesis aimed to identify, describe, and understand the educational processes inherent to the social practice of leisure that emerge from the memories of former participants of the project. The research adopted a qualitative approach, grounded in phenomenology (situated-phenomenon modality), and involved semi-structured interviews with 24 former project participants. After transcription and careful readings of the interviews, phenomenological reduction and nomothetic analysis procedures were applied, from which three thematic categories emerged. The first category, “Leisure as a Lived Right: The Role of VADL in Participants’ Lives,” reveals how VADL dismantled historical barriers that limit access to leisure. The participants described the project as a space for the democratization and re-signification of leisure, recognizing it as both a right and a form of resistance against social inequalities. The second category, “Learning to Be More: Knowledges Constructed within VADL,” brings to light the multiple learnings fostered by the project. These learnings went beyond technical skills, encompassing ethical, social, and cultural values that impacted the life trajectories of the former participants. VADL emerged as a space for intercultural dialogue, where diverse knowledges were valued and integrated into educational practices. The third category, “Education with Love: Relationships of Trust and Commitment in VADL,” highlights the project’s affective dimension, in which the educators established bonds founded on respect and love. The care and welcoming nature of these relationships were identified by the participants as key to the project’s success, creating an environment of trust and shared responsibility where they felt valued. From these analyses, it is understood that VADL constitutes a space for critical and humanizing learning, in which leisure is experienced as both a right and a transformative social practice. The identified educational processes reveal that the project functioned as a field of resistance and collective knowledge construction, promoting awareness, humanization, and liberation.

El proyecto de extensión universitaria Vivencias en Actividades Diversificadas de Ocio (VADL), vinculado al Departamento de Educación Física y Motricidad Humana de la Universidad Federal de São Carlos (UFSCar), tiene como objetivo la educación por y para el ocio de niños y adolescentes entre 7 y 17 años, procedentes de comunidades vulnerables de São Carlos, interior del estado de São Paulo, Brasil. Basado en los principios de la Educación Popular, el VADL desarrolla actividades que valoran las relaciones étnico-raciales, de género, intergeneracionales y ambientales. Su referencial teórico-metodológico articula la Pedagogía Dialógica, la Ciencia de la Motricidad Humana, la Fenomenología Existencial y la Ecología de Saberes. La presente tesis doctoral tuvo como objetivo identificar, describir y comprender los procesos educativos de la práctica social del ocio que emergen de las memorias de los/las participantes-egresados/as del proyecto. La investigación adoptó un enfoque cualitativo, basado en la fenomenología (modalidad fenómeno situado), con la realización de entrevistas semiestructuradas con 24 participantes egresados/as. Tras transcripción y lecturas atentas, se aplicaron los procedimientos de la reducción fenomenológica y del análisis nomotético, a partir de los cuales surgieron tres categorías temáticas. La primera categoría, "El ocio como derecho vivido: el papel del VADL en la vida de los/las participantes", revela cómo el VADL rompió barreras históricas que limitan el acceso al ocio. Los/las participantes relataron el proyecto como un espacio de democratización y resignificación del ocio, reconociéndolo como un derecho y una práctica de resistencia frente a las desigualdades sociales. La segunda categoría, "Aprender a ser más: saberes construidos en el VADL", saca a relucir los múltiples aprendizajes proporcionados por el proyecto. Estas enseñanzas trascendieron el dominio técnico, involucrando valores éticos, sociales y culturales que impactaron las trayectorias de vida de los/las participantes-egresados/as. El VADL emergió como un espacio de diálogo intercultural, donde saberes diversificados fueron valorados e integrados a las prácticas educativas. Ya la tercera categoría, "Educación con amorosidad: relaciones de confianza y compromiso en el VADL", destaca la dimensión afectiva del VADL, en la cual los/las educadores/as establecieron vínculos basados en el respeto y la amorosidad. El cuidado y la acogida presentes en las relaciones fueron señaladas por los/las participantes como fundamentales para el éxito del proyecto, creando un ambiente de confianza y corresponsabilidad, donde los/las participantes se sentían valorados/as. A partir de estos análisis, se comprende que el VADL se constituye como un espacio de aprendizaje crítico y humanizador, en el cual el ocio es vivido como derecho y como práctica social transformadora. Los procesos educativos identificados revelan que el proyecto operó como campo de resistencia y construcción colectiva de saberes, promoviendo concientización, humanización y liberación.
Leisure and popular education: perspectives of former participants of a social project
Ocio y educación popular: perspectivas de participantes egresados/as de un proyecto social
Keywords: Processos educativos; Lazer; Educação popular; Extensão universitária; Projeto social; Educational processes; Leisure; Popular education; University extension; Social project; Ocio; Educación popular; Extensión universitaria; Proyecto social; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS DA SAUDE::EDUCACAO FISICA